Three new Nannastacidae (Crustacea: Cumacea) species from a Caribbean mesophotic ecosystem - Petrescu, Iorgu; Chatterjee, Tapas; Schizas, Nikolaos V. (Zootaxa, 2014)
Examination of substrata from the mesophotic reefs of Mona Island, Puerto Rico yielded 3 new species of cumaceans, all from the family Nannastacidae: Cumella achimae sp. nov., C. victoriae sp. nov. and Nannastacus craciuni sp. nov. The 3 new species bring the total of new cumacean taxa described from the mesophotic reefs of US Caribbean to 9, highlighting the potential of mesophotic reefs as a biodiversity hotspot. For the first time we report the genus Nannastacus from the Caribbean Sea.